A soberania e os direitos humanos Sovereignty and human rigts - Celso Lafer (Lua Nova: Revista de Cultura e Política, 1995)
À suposição hobbesiana de que não há limites éticos ao subjetivismo das soberanias, no plano internacional, podem se contrapor dois modelos, um inspirado em Grocio e o outro em Kant. Somente o modelo kantiano é capaz de reconhecer plenamente a universalidade dos direitos humanos e responder aos desafios que as tendências centrípedas (produzidas pela globalização econômica) e centrífugas (originadas dos nacionalismos e particularismos étnicos e religiosos de todo tipo) apresentam à convivência internacional. The Hobbesian claim that in international relations there is no way of submitting the subjectivism of the sovereingties to ethical constraints may be rejected on either Grotius' or Kant's terms. But only a broadly Kantian approach is able to recognize the universality of human rights and to meet two kinds of challenge to international coexistence: those related to the centripetal forces of global economic interdependence and those related to the centrifugal forces arising from the sharpening of national, ethnic and religious differences.